Afterword: The Work of Culture, Heritage, and Musealized Spaces in "Unprecedented Times". Issue 1 (1st July 2020) - Kreps, Christina
Abstract: Writing at the midpoint of 2020, it has become cliché to say we are living in unprecedented times as the world copes with a confluence of events and challenges near cataclysmic proportions—the COVID-19 pandemic, civic unrest, social and political upheavals, and disrupted economies. In these times, what should be the work of culture, heritage, and musealized spaces and those that study them? I reflect on the articles in the special section, which stand as examples of engaged research and scholarship that seek to make visible troubled histories and presents, and to amplify voices that have for too long been silenced or ignored. Such visibility work surfaces what does and does not have precedent, what has and has not changed, and what is truly different and revolutionary. The articles draws on historical, comparative, and global perspectives to enrich knowledge gained from firsthand observation and engagement with local communities. Using Donna Haraway's concept of "tentacular thinking, " I argue that we need not only to shed light on difficult chapters in our histories, but also to offer tools for understanding, guidance, and thoughtful actions in the present.